Subacute Thyroiditis: Clinical Presentation and Long Term Outcome - Assim A. Alfadda; Reem M. Sallam; Ghadi E. Elawad; Hisham AlDhukair; Mossaed M. Alyahya (International Journal of Endocrinology)
Few studies have been reported from the Kingdom of Saudi Arabia (SA) to describe the clinical presentation and long term outcomes of subacute thyroiditis (SAT). Our aim was to review the demographic, anthropometric, clinical presentation, laboratory results, treatment, and disease outcome in Riyadh region and to compare those with results from different regions of the Kingdom and different parts of the world. We reviewed the medical files of patients who underwent thyroid uptake scan during an 8-year period in King Khalid University Hospital. Only 25 patients had confirmed diagnosis of thyroiditis. Age and gender distribution were similar to other studies. Most patients presented with palpitation, goiter, and weight change. Elevated thyroid hormones, suppressed thyroid-stimulating hormone, and elevated ESR were reported. Among those, 7 cases of SAT were recorded. β-Blockers were prescribed to 57% and nonsteroidal anti-inflammatory drugs to 29% of SAT. Long follow-up demonstrated that 85.7% of SAT cases recovered, while 14.3% developed permanent hypothyroidism. In conclusion, SAT is uncommon in the central region of SA. Compared to the western region, corticosteroid is not commonly prescribed, and permanent hypothyroidism is not uncommon. A nation-wide epidemiological study to explain these interprovincial differences is warranted.